Action: a bridge between vocational and mental health counselling*. Issue 5 (20th October 2017) - Valach, Ladislav; Young, Richard A.
ABSTRACT: A theory of goal-directed action is proposed as a conceptual link between vocational and mental health counselling. Originally emerging from the vocational counselling field, contextual action theory is presented as a critical conceptual link not only between mental health and occupational life but also between counselling practices in these domains. This specific application of goal-directed action to vocational and mental health counselling is addressed by describing counselling as goal-directed action, the five tasks of counselling it invites, and tools for supporting client goals, such as the self-confrontation interview.